(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the phenological phases of grape varieties such as Charos, Tharini, Tayifi and Rizamat were observed, and the phenophases of these varieties, such as budding and growth of branches, flowering, ripening of fruits, ripening of branches, and the beginning and end of the Khazon phase in vine branches. Studied through field observations.